The diagnosis and management of porphyria cutanea tarda (PCT) - Mojakgomo H. Motswaledi (South African Family Practice)
The porphyrias are a group of disorders in which excessive quantities of porphyrins or their precursors are produced. They are due to abnormalities in the control of the porphyrin-haem metabolic pathway. The porphyrias are classified into acute and chronic. The acute porphyrias are acute intermittent porphyria (AIP), porphyria variegata (PV) and hereditary coproporphyria (HCP). The chronic porphyrias are porphyria cutanea tarda (PCT), erythropoietic protoporphyria (EPP) and congenital erythropoietic porphyria (CEP). They are further classified as hepatic or erythropoietic, depending on the major site of abnormal metabolism. This article is about PCT, which is more common in South Africa than the other porphyrias and is classified as chronic and hepatic.